1990
DOI: 10.1093/jn/120.10.1185
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Effects on Vitamin D Hormone Metabolism and Binding in Guinea Pigs

Abstract: Ascorbic acid deficiency in guinea pigs fed a vitamin D-replete diet caused a moderate reduction of Ca level in serum and bone; 25-hydroxy-cholecalciferol or 25-hydroxyergocalciferol (25-OHD) serum concentration tended to decline; renal 25-hydroxycholecalciferol-1-hydroxylase (1-OHase) activity decreased 50%; and 25-hydroxycholecalciferol-24-hydroxylase activity increased 1.6-fold. Chromatin 1,25-dihydroxycholecalciferol [1,25-(OH)2D3] receptor concentration in the intestinal mucosa decreased 20-30%, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…GSH ester slowed the disappearance of osteoid material characteristically seen in scurvy. In addition to the well-studied effect of scurvy on hydroxylation reactions involved in collagen synthesis, recent work suggests that ascorbate-dependent hydroxylation may also be closely connected with vitamin D metabolism and formation of bone (29).…”
Section: Discussionmentioning
confidence: 99%
“…GSH ester slowed the disappearance of osteoid material characteristically seen in scurvy. In addition to the well-studied effect of scurvy on hydroxylation reactions involved in collagen synthesis, recent work suggests that ascorbate-dependent hydroxylation may also be closely connected with vitamin D metabolism and formation of bone (29).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D status should be carefully defined as sufficient, insufficient, or deficient based on mechanistic studies and direct and indirect evidence-based approach. The US Institute of Medicine (IOM) [22,23], the Endocrine Society [24], the European Food Safety Authority [25], and health regulatory agencies of other European countries [26,27] [1,26,29,30]. Extra-renal production of 1,25(OH) 2 D 3 and its possible significance for paracrine/autocrine regulation of cellular functions is plausible [1,3], but this production does not appear to contribute to maintaining circulating 1,25(OH) 2 It is also worth mentioning that rickets and osteomalacia are observed when 25(OH)D is "undetectable" in blood (usually, it means below 0.5-5 ng/mL depending on the assay) and that the optimal bone growth and remodeling as well as maximum intestinal Ca 2+ absorption [the major physiological functions of 1,25(OH) 2 D 3 ] can be maintained in healthy individuals at 25(OH)D concentrations in the range of 10-20 ng/mL [probably, the lower limit is sufficient because it will not limit the 1,25(OH) 2 D 3 production].…”
Section: Introductionmentioning
confidence: 99%
“…However, supplementation of the diet of two strains of 71-week-old hens (LB Brown and LSL White) with 2 mg/kg calcitriol for 8 weeks lowered the rate of damaged eggs and concurrent use of 100 mg/ kg ascorbic acid further decreased shell breakage (Weiser et al, 1992). The dramatic response to ascorbic acid was ascribed to its synergistic role in the hydroxylation of cholecalciferol (Weiser et al, 1988), similar to the response observed in guinea pigs (Sergeev et al, 1990) and the terminal differentiation of cultured chondrocytes through promotion of calcitriol synthesis (Farquharson et al, 1998). Based on the response of old hens to ascorbic acid (Weiser et al, 1992) it was postulated that weak shells towards the end of the production cycle may be the result of decreased biosynthesis of ascorbic acid, decreased tissue ascorbic acid, and the downstream consequences on synthesis of calcitriol.…”
Section: Introductionmentioning
confidence: 54%